2014
DOI: 10.1071/cp13295
|View full text |Cite
|
Sign up to set email alerts
|

Wheat biomass and yield increased when populations of the root-lesion nematode (Pratylenchus thornei) were reduced through sequential rotation of partially resistant winter and summer crops

Abstract: The root-lesion nematode, Pratylenchus thornei, can reduce wheat yields by >50%. Although this nematode has a broad host range, crop rotation can be an effective tool for its management if the host status of crops and cultivars is known. The summer crops grown in the northern grain region of Australia are poorly characterised for their resistance to P. thornei and their role in crop sequencing to improve wheat yields. In a 4-year field experiment, we prepared plots with high or low populations of P. thornei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…These relationships were still evident at the low population densities for Experiments 1 and 2 (2,570 and 975 P. thornei /kg soil) but not so for Experiment 3 (578 P. thornei /kg soil). These results are in line with previously established thresholds for grain yield loss taken to be 2,000 P. thornei /kg soil at any depth interval in the soil profile (Thompson et al, ) or 1,000 P. thornei /kg soil averaged over a soil profile of 0.9 m depth (derived from Figure b; Owen et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These relationships were still evident at the low population densities for Experiments 1 and 2 (2,570 and 975 P. thornei /kg soil) but not so for Experiment 3 (578 P. thornei /kg soil). These results are in line with previously established thresholds for grain yield loss taken to be 2,000 P. thornei /kg soil at any depth interval in the soil profile (Thompson et al, ) or 1,000 P. thornei /kg soil averaged over a soil profile of 0.9 m depth (derived from Figure b; Owen et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…This pest has forced many growers to grow tolerant wheat ( Triticum aestivum ) cultivars to minimise potential yield losses which can be up to 70% (Thompson, Brennan, Clewett, Sheedy, & Seymour, ). Correct diagnoses of nematode populations, the use of tolerant wheat cultivars and rotations with resistant crops (Owen, Clewett, Bell, & Thompson, ) have reduced the impact of P. thornei from a potential loss of AUD$104 million/year to an actual loss of $38 million/year (Murray & Brennan, ). Continued research and development is required to further reduce yield loss.…”
Section: Introductionmentioning
confidence: 99%
“…thornei population densities in the topsoil after wheat maturity and to the pattern of soil profile distributions of P . thornei in some fallow fields where maximum population densities can occur in the subsoil layers at various depths to 60 cm (Thompson et al , ; Owen et al , ). Wilson et al () showed that the rate of evaporation of soil water at high initial contents equalled the potential evaporation from a free water surface for all three soils studied (namely a sand, a silt and a clay soil).…”
Section: Discussionmentioning
confidence: 99%
“…Other hosts of P. thornei among crop species grown in this region include winter crops barley, triticale (×Triticosecale), durum (Triticum turgidum ssp. durum), and faba bean (Vicia faba), and summer crops mung bean, black gram (Vigna mungo) and soybean (Glycine max) (Owen et al, 2012(Owen et al, , 2014. Management of P. thornei for wheat production depends on crop sequences that include moderately resistant crop species like sorghum (Thompson et al, 2008(Thompson et al, , 2012aOwen et al, 2014), which is the major summer crop species in the subtropical grain region of Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Fixed rotations are difficult to implement due to variable rainfall patterns in this region, and flexible crop sequencing (termed opportunity cropping) is often practiced. Pratylenchus thornei survives well in the clay soils of the region and, following growth of a susceptible wheat cultivar, ~3 years of fallow and/or resistant rotational crops are needed to reduce high nematode population densities to below the threshold for damage (Owen et al, 2014;Whish et al, 2017) which is ~2,000 nematodes/kg soil for intolerant wheat cultivars (Thompson et al, 2008). Protection of the major at-risk crops through breeding resistant and tolerant genotypes is essential for the long-term management of P. thornei in this region.…”
Section: Introductionmentioning
confidence: 99%